(untitled) - Kernighan, Brian W. (Boston, 1999)
The practice of programming is more than just writing code. Programmers must also assess tradeoffs, choose among design alternatives, debug and test, improve performance, and maintain software written by themselves and others. At the same time, they must be concerned with issues like compatibility, robustness, and reliability, while meeting specifications.
Lập trình căn bản A
Keywords: Computer programming,Lập trình máy tính